2016
DOI: 10.1016/j.ifacol.2016.07.138
|View full text |Cite
|
Sign up to set email alerts
|

LabVIEW Perturbed Particle Swarm Optimization Based Approach for Model Predictive Control Tuning

Abstract: In this paper, a new Model Predictive Controller (MPC) parameters tuning strategy is proposed using a LabVIEW-based perturbed Particle Swarm Algorithm (pPSA). This original LabVIEW implementation of this metaheuristic algorithm is firstly validated on some test functions in order to show its efficiency and validity. The optimization results are compared with the standard PSO approach. The parameters tuning problem, i.e. the weighting factors on the output error and input increments of the MPC algorithm, is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…The convergence and parameters selection of this algorithm are proved [22]. PSO theory has been enormously successful in various industrial domains, but more significantly in control and optimal engineering design as shown in [21], [22].…”
Section: Overviewmentioning
confidence: 93%
See 1 more Smart Citation
“…The convergence and parameters selection of this algorithm are proved [22]. PSO theory has been enormously successful in various industrial domains, but more significantly in control and optimal engineering design as shown in [21], [22].…”
Section: Overviewmentioning
confidence: 93%
“…Eberhart [20]. This advanced global technique is inspired by the swarming behavior of biological populations [21]. In comparison with an others methods of metaheuristics, this optimization technique it is a simple concept, it is computationally efficient algorithm and easy to implement.…”
Section: Overviewmentioning
confidence: 99%
“…These control laws are updated at each sampling time k in order to minimize the cost function (1) under various operational constrains [5,6,23]:…”
Section: A Formalism and Basic Conceptsmentioning
confidence: 99%
“…Demonstrative results and analyses are given and discussed through this subsection. The position dynamics of the metal sphere of MAGLEV system is modeled as follows [28,29]: (23) Since that the MAGLEV 33-006 system is SISO type, the unknown weighting matrices Q and R of the MPC approach are scalars. Therefore, the formulated optimization problem (5) has four decision variables, i.e.…”
Section: A Case-study 1: Magnetic Levitation Systemmentioning
confidence: 99%
See 1 more Smart Citation